Evaluation of growth regulators asthinners on 'Thompson Seedless' table grapes clusters - Arancibia Urzúa, Gonzalo Nicolás; Callejas Rodríguez, Rodrigo; Meza, Gabino Reginato (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
In order to evaluate in the Region de Atacama and Region Metropolitana from Chile, the use of complementary thinners to the gibberellic acid (GA3) applied to 'Thompson Seedless' grapes. This research explored the use of naphthalene acetic acid (NAA), thidiazuron (TDZ) and benzyladenine (BA) applied to flowering plants; and WuxalÂ® Ca in the fruit set. During the first season, prospective assays were performed. NAA was sprayed at: 0; 2.5; 5; 7.5; 10 and 12.5 mg"¢L-1; BA tested concentrations were: 0, 60, 90, 120, 150 and 180 mg"¢L-1, and TDZ concentrations were: 0; 0.5; 1; 1.5 and 2 mg"¢L-1. During the second season, NAA was sprayed at 0; 2.5; 5.0 and 7.5 mg"¢L-1 and BA was applied at 0, 150, 300, 450 and 600 mg"¢L-1. On a thirth trial, 2 mg"¢L-1 of NAA and WuxalÂ® Ca applied at bloom and fruit set, respectively. NAA decreased the number of berries for cluster; phytotoxicity was detected at concentration since 7.5 mg"¢L-1. BA increased berry number with higher concentrations. TDZ did not show differences in thinning. WuxalÂ® Ca applied after NAA, decreased berry number per cluster, extending the effective period of thinning until after fruit set.